Kebolehpercayaan pelaporan maklumat alam sekitar di Malaysia - Romlah Jaafar; Nordin @ Jusoh Mohammad; Takiah Mohd. Iskandar (Environmental Management Society, Malaysia, 2002)
Information on company’s environmental performance needs to be reported as they are relevant and required by various stakeholders as a basis for decision- making, either for economic or social reasons. However, information reporting is still limited among Malaysia companies, especially in their financial and annual reports. This is because information reporting is neither required by legislation nor accounting standards. This study deals with environment information reporting by companies that have been found to cause environmental problems. The result shows that environmental information reporting by these companies are incomplete and one sided, and the actual environmental performance of the company is not reported. Therefore the validity of the information on the company’s environmental performance as reported is suspect. The government should scrutinize the issue of validity of information reporting in the annual report in order to overcome the problem of information trustworthiness